Pemanfaatan Sampah Botol Bekas berbasis Ramah Lingkungan sebagai Media Tanam Sayuran di Kelurahan Antirogo - Novita, Tri; Karima, Alfin Kamilia; Rahmawati, Dewi; Fatima, Dewi Restiana; Haryudha, Dony Putra; Pratiwi, Fadila Yanuri; Hasanah, Lika Lailatul; Amri, Muhammad Qoyyimul; Ridwan, Muhammad; Kusumawanti, Putria; Satotoputra, Raden Bagaskara Septiawan; Kusuma, Radhinaer Irsya; Rumapea, Rahel Aprilia Omas; Hadi, Samsul; Helmy, Sulthan Rafly (LPPM STKIP PGRI Pacitan, 2024)
Garbage is a serious problem in Indonesia. It is not surprising that there is a lot of waste found in various places, such as used plastic bottles. To overcome this problem, the Collaborative KKN Team #2 237 invites the community to manage and utilize used bottle waste as a medium for growing vegetables in the Antirogo Village. This activity aims to minimize the volume of bottled waste in the surrounding environment and educate the public to utilize used bottled waste as a medium for growing vegetables. The method used in the implementation of this activity is through socialization and joint manufacturing practices. The results of this study indicate that the audience is enthusiastic in receiving the material provided and the results of the questionnaire indicate that the audience's high desire to practice it at their homes on an ongoing basis. This is of course as one of the results of the successful activities received by the Collaborative KKN #2 237 teams